SHOPEE PAY LATER SCHEME: ASSESSING UNDERSTANDING OF UITM DUNGUN STUDENT - Aminullah, Nur Wajihah; Daud, Mohd Ariff Mohd (Jurnal ’Ulwan, 2024)
The emergence of various payment systems has brought convenience to the community for shopping. One of the payment systems that people love is Shopee Pay Later which was introduced by Shopee as a new addition to their payment method. This system allows the buyer to get the goods first and pay later. This study seeks to investigate the perception of UiTM Dungun’s students as students are more exposed to the online shopping system. This study will identify factors that may influence the interest of UiTM Dungun students to use Shopee Pay Later. In addition to that, this research also seeks to assess their level of understanding of the Shopee Pay Later system. This study used both qualitative and quantitative methods. 3 students were interviewed to gain deep insight into the matter. Additionally, 61 questionnaires were distributed to UiTM Dungun’s students and their responses were analyzed. It was discovered that most of the students were aware of the concept of the Shopee Pay Later payment method.